Implementing multi criteria decision making methods for computing complexity involved in industrial investment castings - Maheta, Nikunj; Sata, Amit (Mechanical Engineering Advances, 2024)
Investment casting is admired for its ability to produce industrial castings with remarkable precision, exceptional exterior finish and complex designs among diverse industrial application. Traditionally, the complexity of these castings is generally assessed qualitatively while quantitative measurement of this complexity remains largely unexplored. To identify the various parameters that affects the complexity of industrial investment casting, an in-person industrial survey was carried out in one of the major investment casting clusters that accounts for nearly 25% of India’s investment casting foundries. Through this survey it was found that complexity of investment casting is determined by three factors related to geometry, features and manufacturability. These three factors are further driven by 19 elements and 52 attributes. These 52 attributes are further characterised by 212 meta-attributes. This research focuses on applying multi-criteria decision-making methods to quantify the complexity affects in manufacturing industrial investment castings. Numerous methodologies within the domain of Multi-Criteria Decision-Making (MCDM) have been explored to determine the appropriate weightage for the factors, elements, attributes and meta-attributes involved. It was observed that for the specific problem mentioned, the Weighted Criteria Approach (WCA) and Analytical Hierarchy Process (AHP) were identified as suitable choices, aligning well with the required level of accuracy. The result obtained through these methods were used to compute the complexity of industrial castings. The proposed complexity index was validated using various industrial castings and proved to be a valuable tool for designers in adopting investment casting process for producing complex castings.